Physical growth of preterm girls with visual impairment - Umławska, Wioleta (Anthropological Review, 2007)
The aim of this study was to estimate pubertal age and to assess the level of physical development of preterm girls with defective vision. The study material - anthropometric data (body height and weight, BMI) and information on the age of menarche were collected from 155 subjects with defective vision (partially sighted and blind). Median age at menarche was estimated by probit analysis. The girls, ranging in age from 7-18 years, attended Centers for Blind and Partially Sighted Children in Wroclaw and Cracow (Poland). 22% of the subjects were prematurely born, were born with low birth mass and their sight defect diagnosed as retinopathy due to prematurity (ROP). The girls with ophthalmic impairments were shorter and lighter than their age peers from the reference data. Blind girls reached pubertal age 2 months earlier than the partially sighted (Me=13.31 and Me=13.44) and, the preterm subjects entered puberty 6 months earlier than the full-term girls, irrespective of degree of defect (Me=12.93 and Me=13.42, respectively). The results suggest that earlier puberty is associated with visual impairment. The results show also that irrespective of the degree of defect, preterm girls reach menarche significantly earlier than those who were full-term. It seems possible that mechanisms responsible for earlier puberty in the preterm subjects and with low body mass play an important a role in sexual maturation in girls with sight dysfunction. There appears to be a need to pursue further studies in this sphere.